Education Of Small And Medium Enterprise (Sme) Workers On Processed Chips Related To Low Back Pain (Lbp) As An Effort To Prevent - Damas Tsaniyah Min Rohmatillah; Annisa Tri Andriani; Alif Nur Azka; Maghfiri Shania Bidari; Manuel Umbu Madiaha (Universitas Muhammadiyah Malang, 2025)
Every year around 380,000 workers die due to workplace accidents or occupational diseases (PAK). Factory workers, workers in the culinary sector, and jobs that involve a lot of repetitive movements have a fairly high risk of PAK. Occupational factors are risk factors for Low Back Pain (LBP), namely excessive use of muscles, repetitive movements over long periods of time, movements with force, and static work postures for long durations of time. The aim of this service is to prevent the occurrence of LBP through education regarding LBP among Zaha workers. This paper is a cross-sectional descriptive study among 3